Food environment in Burkina Faso: priority actions recommended to the government using Food-EPI tool - Tapsoba, Viviane Aurelie; Compaore, Ella W. R.; Zeba, Augustin Nawidimbasba; Some, Jerome Winbetourefa; Manga, Julien Soliba; Diouf, Adama; Moubarac, Jean-Claude; Vandevijvere, Stefanie; Dicko, Mamoudou Hama (Frontiers in Nutrition, 2024)
The food environment is an important factor in the efforts of countries worldwide to achieve a transition to sustainable food systems. The objective of this study is to formulate and prioritize actions to be addressed to the government of Burkina Faso for the creation of a healthy food environment, which will contribute to reducing malnutrition in all its forms and noncommunicable diseases.Methods: National experts were brought together to identify and prioritize actions to fill the gaps identified through a multi-step assessment process following the methodology of the Healthy Food and Environment Policy Index (Food-EPI).Results: Up to 20 priority policy actions were recommended to the Burkina Faso government.Actions in the policy component focused mainly on regulation of food promotion and marketing, particularly to children, and others in the infrastructure support component focused largely on political leadership, i.e. strong and visible political support from the government to improve the food environment, population nutrition, diet-related non-communicable diseases and their inequalities.The priority actions to be recommended to the government will strengthen advocacy for government decisions to create a healthier food environment in the country.